2017
DOI: 10.1016/j.ecolind.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable intensification – “oxymoron” or “third-way”? A systematic review

Abstract: Sustainable Intensification (SI) is a term that has been advanced to capture a concept that some consider as the 'third paradigm' for global agricultural development. However, the term has become subject to intense debates as well as scepticism and confusion regarding its meaning and the characteristics of production systems that could indicate SI (defined as "indicators"). This has resulted in a proliferation of literature. We have conducted a systematic review of a sample of this literature analysing the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 110 publications
1
80
0
3
Order By: Relevance
“…an ostensible self-contradiction, because intensification cannot be achieved in a sustainable way. Sustainable intensification suggests an acceptable practice for something that cannot be achieved or maintained, based on the fact that metrics are used that do not take into account important negative elements in the economic and ecological cost-benefit equation (Mahon et al 2017). The question is whether there is a way out of this quagmire and whether we, given the obvious problems with clearly defining it, can circumscribe sustainable intensification in useful ways.…”
Section: Sustainable Intensificationmentioning
confidence: 99%
See 2 more Smart Citations
“…an ostensible self-contradiction, because intensification cannot be achieved in a sustainable way. Sustainable intensification suggests an acceptable practice for something that cannot be achieved or maintained, based on the fact that metrics are used that do not take into account important negative elements in the economic and ecological cost-benefit equation (Mahon et al 2017). The question is whether there is a way out of this quagmire and whether we, given the obvious problems with clearly defining it, can circumscribe sustainable intensification in useful ways.…”
Section: Sustainable Intensificationmentioning
confidence: 99%
“…(i) Scientific consensus on (the hierarchy of) sustainability issues at stake, including indicators (Mahon et al 2017), that can be applied to the diversity of farm types present and can capture aspects at different scales across time and space, but can also consider different dimensions (ii) Societal debates resulting in shared values and norms to be taken into account (iii) Institutional innovation to realize adaptive management and governance Jackson et al (2010) put emphasis on the capacity to change and claimed that "rapid changes in land use, food systems, and livelihoods require social-ecological systems that keep multiple options open and prepare for future unpredictability. We therefore need "sustainagility": "the properties and assets of a system that sustain the ability (agility) of agents to adapt and meet their needs in new ways"".…”
Section: Defining Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Since SI is generally considered to be a goal, rather than a defined aim, methods for achieving it are relatively undefined (Mahon et al., ; Petersen & Snapp, ; Wezel, Soboksa, McClelland, Delespesse, & Boissau, ). In a review of indicators used to measure SI, Mahon et al.…”
Section: Introductionmentioning
confidence: 99%
“…In a review of indicators used to measure SI, Mahon et al. () found that many are very loosely defined, which has led to an under‐appreciation of social implications, and a lack of specificity over the rationale, scale, and farm type for which SI is proposed. Many research articles on SI have focused on debating the usefulness of the term, and on refining definitions, at the expense of developing a set of SI practices that could lead to practical gains.…”
Section: Introductionmentioning
confidence: 99%